Description of Maunder-like events from a stochastic Alpha–Omega model - Gomez, Daniel Osvaldo (2006)
One of the most impressive solar phenomena is its magnetic activity cycle. The number of sunspots observed in the solar surface varies with a period of approximately 11 years. Superimposed to this cyclic behavior, there are sporadic events such as the Maunder minimum, during which very few sunspots were detected. In the present work, an Alpha–Omega dynamo model is proposed to study these phenomena. We use velocity profiles of the solar interior obtained from helioseismology, which include differential rotation (the X-effect), a meridional flow and the turbulent velocity field of the convective region (the a-effect). By simulating the helicoidal and disordered flow of the giant cells through a stochastic component in the a coefficient, we reproduce not only the periodic behavior of the solar cycle, but also sporadic events such as the Maunder minimum. This model suggests the existence of a link between giant cell fluctuations and the irregularities observed in the solar cycle, such as north–south asymmetries and secular variations like the Maunder minimum.